Mutagens affect food and water biodeteriorating fungi - Paterson, R. R. M. (2015)
Many areas of food mycology could be affected detrimentally by mutation of wild type fungi. Some of these will contact mutagens from pre-isolation to experimentation and the effect on fungi isolated from mycotoxin-contaminated food is assessed for the first time in this review. However, this mutagen issue is not considered by other authors in primary research papers, which is relevant to molecular biology techniques for gene sequencing, phylogenetics, diagnostics and mycotoxin production. The presence of mutagens is anathema to methods for DNA analysis at the experimental design level and concepts such as cryptic species and correlating anamorphs with teleomorphs are affected. Strains held in culture collections may be artifacts. Methods to ameliorate the problem are provided herein.